Identifying the Optimal Climatic Zones for the Restoration of Oak Forests in Kermanshah Province - Mohammad Baaghideh; Alireza Entezari; Yazdan Babaei; Mohsen Abbasini (جغرافیا و پایداری محیط)
Climateisone of themost importantfactors affecting thehuman environment and activities. Nowadays,the development ofurban and industrialcenters, and maintaining and increasing forest resources requires an increase in the informationindifferentclimaticzones. Althoughlarge-scaleweathersystemshave the same influence on different parts of KermanshahProvince, this province experiencesmany various localclimates too. So thatthese difference has caused thepresence or absence ofvegetation indifferent regionsof the province .In order toidentifyclimatic areas and adapted vegetations in each area, statistical methodssuch asfactor analysisandclusteringwas used and 34 climate parameters were selected from 16 meteorologicalstations in thisprovince. Then, (IDW) method was used to interpolatevariablesacross the province and the data matrix size was obtained as 34 × 62. Factor analysis and an agglomerative hierarchical cluster analysis through ward linkage method was applied to it. The results show that there are 7 factors which control the climate of Kermanshah: temperature, wind and precipitation direction, moisture, thunderstorm, wind & dust, shower and cloud. Also clustering technique recognized seven sub climatic regions and the most extensive oak habitat was identified in the foothills regions and the main factor in this regard was the wind-precipitation direction.